2018
DOI: 10.1016/j.dib.2018.06.048
|View full text |Cite
|
Sign up to set email alerts
|

Dataset for regulation between lncRNAs and their nearby protein-coding genes in human cancers

Abstract: This article contains data related to the research article entitled “Systematic analysis reveals long noncoding RNAs regulating neighboring transcription factors in human cancers” (Liu et al., 2018 in press) [1]. Long noncoding RNAs (lncRNAs) are proposed to play essential roles in modulating the expression of the nearby loci. In this study, we systematically investigated the relationship between lncRNAs and their neighboring genes based on the genomic location of genes and the transcriptome expression profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 8 publications
0
8
0
1
Order By: Relevance
“…Long noncoding RNAs (lncRNAs) are considered a type of non-coding RNAs consisting of more than 200 nucleotides without coding protein potential [10]. More and more researches suggested lncRNAs are involved in human cancer development by regulating tumor cell proliferation, apoptosis, cell-cycle, migration, invasion, and autophagy [11,12]. Long intergenic noncoding RNA 00511 (LINC00511, also known as onco-lncRNA-12), is a newly identified carcinogenic lncRNA that maps to chromosome 17q24.3 [13].…”
Section: Introductionmentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs) are considered a type of non-coding RNAs consisting of more than 200 nucleotides without coding protein potential [10]. More and more researches suggested lncRNAs are involved in human cancer development by regulating tumor cell proliferation, apoptosis, cell-cycle, migration, invasion, and autophagy [11,12]. Long intergenic noncoding RNA 00511 (LINC00511, also known as onco-lncRNA-12), is a newly identified carcinogenic lncRNA that maps to chromosome 17q24.3 [13].…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs are well acknowledged to mediate gene transcription and recent research attention has been attracted to their implication in tumorigenesis due to their crosstalk with neighboring transcription factor genes 25,26. In our study, we found that lncRNA TMPO‐AS1 could bind to E2F6 to interrupt the binding between E2F6 and LCN2, by which the LCN2 expression was activated.…”
Section: Discussionmentioning
confidence: 63%
“…Measurement data (mean ± standard deviation) among multiple groups were assessed by one-way ANOVA, followed by Tukey's post hoc test and those in relation to time-based measurements within each group were assessed by repeated measures ANOVA, followed by Tukey's post hoc test neighboring transcription factor genes. 25,26 In our study, we found that lncRNA TMPO-AS1 could bind to E2F6 to interrupt the binding between E2F6 and LCN2, by which the LCN2 expression was activated. Similar transcription factor-associated lncRNAs mechanism has been validated in connection with overall survival, disease-free survival, and progression-free survival of patients with ovarian cancer.…”
Section: Silencing Of Lncrna Tmpo-as1 Inhibited the Tumorigenesis And Angiogenesis Of Ovarian Cancer Cells In Vivo Through Downregulationmentioning
confidence: 62%
“…LncRNAs are proposed to play essential roles in regulating the expression of the nearby loci [ 38 ]. To probe the interaction between DARS-AS1 and its nearby gene DARS in CC, we first employed GEPIA 2 database to analyse the correlation between their expression in CC tissues.…”
Section: Resultsmentioning
confidence: 99%